0092 Clinical risk reduction in simulated settings (CRRISIS): An initial 2-year experience implementing a hospital-wide simulation programme in a cardiothoracic centre. (2nd November 2015) - Hutchinson, Kate L; Abayalingam, Mayavan; Butcher, Charles; Sarang, Zubair; Green, Rebecca; Hickman, John; Patterson, Colin; Barnett, Alice; Bishop, Jeremy; Raja, Shahzad; Rosenberg, Alex; Lane, Rebecca; et al.
Abstract : Background: The management of patients in a cardiothoracic centre requires effective interaction between clinical care groups. CRRISiS (Clinical Risk Reduction in Simulated Settings) was developed to support this. These high-fidelity, simulation sessions involve the multidisciplinary-team across departments. A debrief structure focussing on human factors and clinical outcomes facilitates a 'common debrief language' across departments. We report participant feedback from our first 2 years. Methodology: 43 training sessions were delivered across cardiology, transplant, intensive care and cardiothoracic departments. All staff were encouraged to attend and signed consent forms. Sessions commenced with an introduction to crisis resource management principles. A structured, step-wise, immersive simulation followed with events occurring in real time, with staff participating in their clinical roles. Scenarios were based on a previously challenging clinical situation or "never events". These included cardiac tamponade and fluoroscopic failure during primary angioplasty. Each scenario was followed by a debrief, facilitated by a simulation instructor, reflecting on both clinical and human factors. The simulation team included teaching fellows, resuscitation officers, allied healthcare professionals and consultants. Feedback was collected using Likert Scale. Results: 202 responses were analysed (16 physiologists, 13 radiographers, 8 students, 3 healthcare assistants, 7 physiotherapists, 50 nurses, 30 junior doctors, 6 registrars, 6 consultants, 68 other/unknown). Group sizes varied from 4–23 staff. 99.5% agreed/strongly agreed that the scenario felt realistic and they had increased awareness of human factors. 99.2% felt they had increased their clinical knowledge and enhanced inter-professional relationships. 99.5% would recommend to colleagues and like to attend more sessions. Conclusions: Implementation of a formal simulation-training programme across a specialist centre is possible. Although it is difficult to assess whether attendance at CRRISiS sessions impacts upon clinical outcomes, candidates have reported improvements in awareness of human factors, clinical knowledge and inter-professional relationships. Moving forward, this may have positive implications for patient care.